2017
DOI: 10.2319/031317-189.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maxillary central incisors on the noncleft and cleft sides in patients with unilateral cleft lip and palate—Part 2: Relationship between root resorption, horizontal tooth movement, and quantity of grafted autogenous bone

Abstract: Objective: To evaluate the relationship between external apical root resorption (EARR) of the maxillary central incisors (U1), horizontal orthodontic tooth movement, and quantity of grafted bone in subjects with unilateral cleft lip and palate (UCLP) over an average duration of 8 years. Materials and Methods: Thirty subjects with UCLP were evaluated for EARR of U1 after edgewise treatment (T2). The teeth were classified as having no EARR, moderate EARR (combined into ''no/ moderate'' EARR), or severe EARR. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A recent study found that cleft-adjacent U1 exhibited more severe external root resorption after orthodontic treatment. 18 The risk of irreversible damage to the root and supporting tissues should also be conveyed to patients and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that cleft-adjacent U1 exhibited more severe external root resorption after orthodontic treatment. 18 The risk of irreversible damage to the root and supporting tissues should also be conveyed to patients and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Among all three studies that used 2D quantitative assessment, only the study by Dhayashankara et al found that the PRF group had better bone height as compared to control group [11]. This positive outcome is explained by the ability of platelet-derived products to speed up bone formation and reduce bone resorption in alveolar cleft bone grafting [11,16,21]. However, this study compared the intervention and control group in a purely descriptive manner without any statistical inference analysis [11].…”
Section: Discussionmentioning
confidence: 89%
“…Unilateral cleft lip and alveolus with or without cleft palate (UCLA ± CP) exhibits delayed or insufficient dental arch and tooth development on the cleft side compared with their noncleft side (Zhang et al, 2016). It has been documented that the development of bilateral teeth and arches, especially the anterior area, is asymmetrical: tooth eruption on the cleft side is delayed, abnormal tooth morphology and size (Zhang et al, 2016), and shorter roots are more frequently observed on the cleft side (Al-Jamal et al, 2010; Maeda-Iino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%